Green Accounting Discourse as an Effort to Mitigate Climate Change Risk in Banks in Pandaan District - Herlinda Nia Audina; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In environmental conservation, accounting plays a crucial role undertaken by companies and other groups. This encompasses interests for public organizations and local companies by companies and other groups. Additionally, environmental accounting also contributes to enhancing effectiveness and productivity in environmental preservation activities by improving internal decision-making processes, such as pricing, controlling overhead costs, and capital budgeting. Qualitative research is utilized to understand and explore this phenomenon using triangulation methods to gather data from various different sources. The research findings indicate that limiting the use of oil-fueled vehicles in Indonesia could be an effort to control climate change, in line with the Paris Agreement, while renewable energy stands as an alternative to be utilized. The UNFCCC has endeavored to regulate the amount or effects of greenhouse gases to limit global temperature rise, with each country expected to set their national contributions to combat climate change. This effort is responded to through UN conferences and results in global agreements, including the Kyoto Protocol and the Paris Agreement, which are legally binding to limit global temperature rise.